Extranodal extension of lymph node metastasis is a marker of poor prognosis in oesophageal cancer: a systematic review with meta-analysis. Issue 11 (7th July 2016) - Luchini, Claudio; Wood, Laura D; Cheng, Liang; Nottegar, Alessia; Stubbs, Brendon; Solmi, Marco; Capelli, Paola; Pea, Antonio; Sergi, Giuseppe; Manzato, Enzo; Fassan, Matteo; Bagante, Fabio; et al.
Abstract : The extranodal extension (ENE) of nodal metastasis is the extension of neoplastic cells through the nodal capsule into the perinodal adipose tissue. This histological feature has recently been indicated as an important prognostic factor in different types of malignancies; in this manuscript, we aim at defining its role in the prognosis of oesophageal cancer with the tool of meta-analysis. Two independent authors searched SCOPUS and PubMed until 31 August 2015 without language restrictions. The studies with available data about prognostic parameters in subjects with oesophageal cancer, comparing patients with the presence of ENE (ENE+) versus only intranodal extension (ENE−), were considered as eligible. Data were summarised using risk ratios (RRs) for number of deaths/recurrences and HRs together with 95% CIs for time-dependent risk related to ENE+, adjusted for potential confounders. Fourteen studies were selected; they followed-up 1437 patients with oesophageal cancer for a median follow-up of 39.4 months. The presence of ENE was associated with a significantly increased risk of all-cause mortality (RR=1.33; 95% CI 1.18 to 1.50, p<0.0001, I 2 =49%; HR=2.72, 95% CI 2.03 to 3.64, p<0.0001, I 2 =0%), cancer-specific mortality (RR=1.35; 95% CI 1.14 to 1.59, p=0.001, I 2 =57%; HR=1.97, 95% CI 1.41 to 2.75, p<0.0001, I 2 =41%) and of risk of recurrence (RR=1.50, 95% CI 1.20 to 1.88, p<0.0001, I 2 =9%; HR=2.27, 95% CI 1.72 to 2.90, p<0.0001, I 2 =0%). On the basis of these results, in oesophageal cancer, ENE should be considered from the gross sampling to the pathology report, and in future oncological staging system.